Reclamation of chemical wastes for the production of efficient concrete modifiers - M M, Kosukhin; I V, Starostina; A M, Kosukhin (International Journal of Engineering and Technology, 2018)
The research concerning the obtaining of highly-efficient polyfunctional superplasticizers for concretes on the basis of chemical production waste with the purpose of their reclamation and improving the environmental situation in the populated areas has been carried out. The highly-efficient concrete admixtures on the basis of various wastes have been synthesized and patented.Â  A new efficient modifier based on pyrocatechin production waste has been suggested. The colloid and chemical properties of the obtained modifier and its influence on physical, mechanical and maintenance-engineering characteristics of concrete have been researched. Its comparative evaluation with the known plasticizing admixtures has been presented. It has been demonstrated that the superplasticizer under study is the most efficient in terms of plasticizing activity and improving the physical and mechanical properties of concretes and concrete mixes and has a polyfunctional effect. Its application allows increasing the concrete mixes flowability and concrete strength, reducing the concrete consumption, providing the concrete with fungicidal properties, cutting the production costs and solving ecological problems of the chemical production waste recycling.Â Â